ANALYSIS OF THE INTERPRETATION OF THE CONCEPT "MORAL VALUES "IN SCIENTIFIC LITERATURE - Yu.O. Zenkovych (Academy of Cognitive and Natural Sciences, 2022)
The article is devoted to the analysis of the various approaches to treatment of concepts of "value" and "moral values" in the scientific literature, that has allowed the author to make a line of generalizations on the given problem.